2015
DOI: 10.1016/j.cub.2015.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Trade-Off between Vocal Tract and Testes Dimensions in Howler Monkeys

Abstract: SummaryMales often face a trade-off between investments in precopulatory and postcopulatory traits [1], particularly when male-male contest competition determines access to mates [2]. To date, studies of precopulatory strategies have largely focused on visual ornaments (e.g., coloration) or weapon morphology (e.g., antlers, horns, and canines). However, vocalizations can also play an important role in both male competition and female choice [3, 4, 5]. We investigated variation in vocal tract dimensions among m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(144 citation statements)
references
References 35 publications
9
133
1
1
Order By: Relevance
“…and Mongolian gazelle, Procapra gutturosa (Frey and Gebler, 2003;; hypertrophied larynges in howler monkeys, Alouatta sp. (Dunn et al, 2015;Kelemen and Sade, 1960), and hammer-headed bats, Hypsignathus monstrosus (Bradbury, 1977); and even an additional, non-laryngeal set of vocal folds (termed 'velar vocal folds') in the koala, Phascolarctos cinereus (Charlton et al, 2013). Other species produce abnormally low formants for their size by extending their vocal tracts using descended and/or mobile larynges (red deer, Cervus elaphus, Reby and McComb, 2003;fallow deer, Dama dama, McElligott et al, 2006; Mongolian gazelle, Procapra gutturosa, Frey et al, 2008; goitred gazelle, Gazella subgutturosa, Frey et al, 2011;koala, Charlton et al, 2011; roaring cats, Panthera sp., Weissengruber et al, 2002), air sacs (black and white colobus monkey, Colobus guereza, Harris et al, 2006) and nasal proboscises (African elephant, Loxodonta africana, McComb et al, 2003;saiga, Saiga t. tatarica, Frey et al, 2007; elephant seals, Mirounga leonina, Sanvito et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…and Mongolian gazelle, Procapra gutturosa (Frey and Gebler, 2003;; hypertrophied larynges in howler monkeys, Alouatta sp. (Dunn et al, 2015;Kelemen and Sade, 1960), and hammer-headed bats, Hypsignathus monstrosus (Bradbury, 1977); and even an additional, non-laryngeal set of vocal folds (termed 'velar vocal folds') in the koala, Phascolarctos cinereus (Charlton et al, 2013). Other species produce abnormally low formants for their size by extending their vocal tracts using descended and/or mobile larynges (red deer, Cervus elaphus, Reby and McComb, 2003;fallow deer, Dama dama, McElligott et al, 2006; Mongolian gazelle, Procapra gutturosa, Frey et al, 2008; goitred gazelle, Gazella subgutturosa, Frey et al, 2011;koala, Charlton et al, 2011; roaring cats, Panthera sp., Weissengruber et al, 2002), air sacs (black and white colobus monkey, Colobus guereza, Harris et al, 2006) and nasal proboscises (African elephant, Loxodonta africana, McComb et al, 2003;saiga, Saiga t. tatarica, Frey et al, 2007; elephant seals, Mirounga leonina, Sanvito et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, through increasing the variability of vocal tract impendence, air sacs might lead to strong non-linear phenomena in vocalizations Riede et al, 2008). Finally, air sacs have been predicted to affect formant frequencies and spacing (Fitch and Hauser, 1995;Fitch, 2000b;Frey et al, 2007;Riede et al, 2008;Dunn et al, 2015), as: (i) air sacs may introduce new resonance frequencies near the resonance frequency of the air sac in isolation, which would be expected to be lower frequency than the resonances of the vocal tract (and would depend on the size and shape of the air sac); and (ii) the original resonances of the vocal tract would be shifted to higher frequencies and closer together (de Boer, 2008(de Boer, , 2009(de Boer, , 2012Riede et al, 2008;Dunn et al, 2015). As a consequence of these acoustic effects, vocalizations produced with air sacs are likely to be louder, more chaotic , contain more resonances and more energy at lower frequencies, and, potentially, be longer and more frequent (de Boer, 2012).…”
Section: The Function Of Air Sacs In Primate Vocal Communicationmentioning
confidence: 99%
“…All of these traits may serve important adaptive functions. Most obviously, perhaps, in situations of competition over access to resources, including mates (Wich and Nunn, 2002;Dunn et al, 2015;Charlton and Reby, 2016).…”
Section: The Function Of Air Sacs In Primate Vocal Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, howler monkeys (Dunn et al, 2015) and koalas (Charlton et al, 2013) produce vocalizations with an unexpectedly low f o given their body size. While the existence of a novel vocal organ explained this observation in koalas (Charlton et al, 2013), in the case of howler monkeys, recent work showed that the low f o of their calls was in theory in accordance with the length of their vocal folds (Dunn et al, 2015). ELE with howler species confirmed this assumption, showing that the f o of vocalizations produced ex vivo matched that of vocalizations produced in nature .…”
Section: Progressive Use Of Excised Larynx Experimentation In a Paralmentioning
confidence: 99%